2014
DOI: 10.1364/oe.22.0a1589
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic integration of GaN-based light-emitting diodes and metal-oxide-semiconductor field-effect transistors

Abstract: In this study, we report a novel monolithically integrated GaN-based light-emitting diode (LED) with metal-oxide-semiconductor field-effect transistor (MOSFET). Without additionally introducing complicated epitaxial structures for transistors, the MOSFET is directly fabricated on the exposed n-type GaN layer of the LED after dry etching, and serially connected to the LED through standard semiconductor-manufacturing technologies. Such monolithically integrated LED/MOSFET device is able to circumvent undesirable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Lau et al have reported monolithic integration of InGaN/GaN light emitting diodes (LEDs) with AlGaN/GaN heterojunction field effect transistors (HFETs) [44] or vertical metal-oxide-semiconductor field effect transistor (VMOSFET) drivers [45], by selective growth of HFET or VMOSFET structures on the LED epilayers, as shown in Figure 6. Alternatively, lateral integration via selective removal of the HFET structure followed by selective growth of the LED structure on top of the exposed GaN buffer layer [46] or selective removal of the LED structure followed by selective growth of the metal-oxide-semiconductor field effect transistor (MOSFET) on top of the exposed n-GaN layer [47] have also been reported. Although it has been demonstrated that the performance of the integrated single LED-transistor chip is comparable to discrete LEDs and transistors [44] fabrication of micro-LED displays using this approach has not yet been reported.…”
Section: Monolithic Fabrication Of Micro-displaysmentioning
confidence: 99%
“…Lau et al have reported monolithic integration of InGaN/GaN light emitting diodes (LEDs) with AlGaN/GaN heterojunction field effect transistors (HFETs) [44] or vertical metal-oxide-semiconductor field effect transistor (VMOSFET) drivers [45], by selective growth of HFET or VMOSFET structures on the LED epilayers, as shown in Figure 6. Alternatively, lateral integration via selective removal of the HFET structure followed by selective growth of the LED structure on top of the exposed GaN buffer layer [46] or selective removal of the LED structure followed by selective growth of the metal-oxide-semiconductor field effect transistor (MOSFET) on top of the exposed n-GaN layer [47] have also been reported. Although it has been demonstrated that the performance of the integrated single LED-transistor chip is comparable to discrete LEDs and transistors [44] fabrication of micro-LED displays using this approach has not yet been reported.…”
Section: Monolithic Fabrication Of Micro-displaysmentioning
confidence: 99%
“…This route can bypass the massive transfer, reduce cost and technological difficulties, and be more reliable in applications. Previously, GaN-based micro LEDs were integrated with GaN high-electron-mobility transistors (HEMTs) [2] or metal-oxide-semiconductor field-effect transistors (MOSFETs) [3]. GaN transistors generally have high breakdown voltages [4,5] and high working frequencies [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Basic functionalities such as light generation, modulation, propagation, and detection can now be fulfilled with a suite of highperformance GaN-based components, including light emitting diodes (LEDs), high electron mobility transistors (HEMTs), waveguides, and photodiodes (PDs), making it possible to accomplish a sophisticated micro-opto-electronic system (MOES) on a chip by monolithic integration [1][2][3]. There has been much progress recently on monolithic integration of GaN-based devices, especially HEMT-LED integration [4][5][6][7]. Monolithically integrated HEMT-LED is a voltage-controlled light emitter, which is simpler to work with in driver design, compared to the conventional current-controlled LEDs.…”
mentioning
confidence: 99%